Number of blood pressure measurements needed for screening of hypertension in children and adolescents - Madarina Julia (Paediatrica Indonesiana, 2009)
Background Routine blood pressure assessment is recommended because childhood hypertension is significantly associated with increased risk of cardiovascular disease in adulthood. However, results of blood pressure measurements in children are highly variable, associated with the risk of under or over-diagnosing in hypertension.Objective To assess the optimal number of measurements to screen elevated blood pressures in children and adolescents.Methods This study used two sets of data, i.e. a dataset from 104 obese and non-obese, male and female primary school-children, and a dataset from 79 obese female adolescents. Blood pressure (BP) was measured using standard techniques described by the fourth report of the National High Blood Pressure Education Program (NHBPEP) Working Group on Children and Adolescents. Elevated BP was defined as systolic and diastolic BP at or above the 90th percentile for gender, age, and height.Results BP measurements taken on day-one were significantlyhigher than those taken on day-two and three. This led tohigher prevalence of elevated BP when only one measurementwas performed. Using the average of two measurements in twooccasions detected elevated blood pressure with specificity andpositive predictive value (PPV) ranged from 0. 74 to 1.0 and 0.58to 1.0, respectively.Conclusions It is necessary to measure blood pressure repeatedly to minimize the risk of over-diagnosing in hypertension in children and adolescents. Using the average of three measurements in three visits is recommended, but drawing conclusions based on two measurements in two occasions have yielded sufficiently high specificity.